Modification of polypropylene mesh by titanium compound: An in Vivo and in Vitro study - Xiao, Yelei; He, Xinyue; Yang, Guang; Li, Huanhuan; Zhao, Yu; Wang, Xuehu (Frontiers in Materials, 2023)
Objective: Previous basic studies on the use of titanized polypropylene meshes in abdominal external hernia repair are not only limited, but also highly controversial. This study aims to investigate the modification effect of titanium compounds on polypropylene materials and compare the performance of two kinds of meshes both in vivo and in vitro. Methods: Human peritoneal mesothelial cells (HMrSV5), human epidermal fibroblasts (HSF), and human monocytic cells (THP-1) were cultured in vitro to simulate the abdominal external hernia environment. Titanized polypropylene meshes (Ti) and polypropylene mesh (Non-Ti) were co-cultured with the cells respectively. The effects of titanium compounds on cell growth were determined by cell activity and apoptosis, and the growth of cells on the mesh surface was assessed using a scanning electron microscope and a confocal microscope. In vivo experiments, different sizes titanized polypropylene meshes and polypropylene meshes were placed between the external oblique abdominal muscle and the internal oblique abdominal muscle, the parietal peritoneum, the serous layer of the descending colon, and the underside of the femoral nerve in rabbits. The effects of titanium compounds were evaluated by observing the anti-adhesion, anti-contraction, anti-fibrotic properties, and effects on nerves of the mesh. Results: Titanium compounds effectively reduced the effects of polypropylene material on cell growth, and improved the fixation and adhesion of HMrSV5, HSF and THP-1 (M0) on the surface of titanized polypropylene meshes. Furthermore, titanium compounds improved the adhesion, contraction and fibrosis of polypropylene material, as well as reduced nerve damage. This improvement demonstrated a regular trend with the type of titanized polypropylene meshes. Conclusions: The titanium compounds improved the biocompatibility of the polypropylene material, which was conducive to the fixation and adhesion of cells on the surface of the meshes, and alleviated the adhesion and contraction of the meshes, and the degree of tissue fibrosis, as well as the influence on nerves.